Concept story in teaching grade 7 biology as a tool to enhance students’ academic achievement (Southeast Asian Journal of Technology and Science, 2022)
This research aims to study the effectiveness of concept story, a novel teaching tool in science education, as an intervention material in teaching Microorganisms to enhance students’ academic achievement in Grade 7 Biology. It is experimental in nature, intending to explore the effect of the said intervention technique to students’ performance. Quantitative approach was utilized to gather the pertinent data and descriptive method to explore the pre-existing and affected conditions. The researcher developed a concept story integrating lesson about microorganisms and used it, administered a validated test and analyzed the results using z-test to reveal the effectiveness of using concept story. Based on the mean test results, it was revealed that the samples performed better on the test compared to the population on the particular content where the concept story was utilized. Therefore, ascertaining that concept story is an effective teaching tool in science to enhance students’ academic achievement. This study was limited only in the effect of using concept story in teaching microorganisms to improve the academic achievement of grade 7 students in Biology. A total of 121 students from the three sections of grade 7 handled by the researcher were the respondents of this study. It was conducted during the second grading period of the school year 2018-2019.